Organizational Agility Based on Automatic Patch Work Behavior in the Era of Environmental Uncertainty - Gunawan, Ahmad; Rahim, Abdul Rahman; Andriyansah, Andriyansah; Fatimah, Fatia (PT Mattawang Mediatama Solution, 2025)
This study focuses on modeling organizational agility based on a synthetic construct, namely automatic patch work behavior, which is proposed, conceptualized, and confirmed by theoretical validation, empirical validation, and nomological validation. The research model involved 219 respondents from the Badan Pusat Statistik (BPS) employees in West Sulawesi Province through cluster sampling techniques accompanied by eligible control of inclusion and exclusion samples, data were obtained using an e-questionnaire in December 2024. Structural equation modeling analysis confirmed that this study was able to present theoretical contributions in the field of strategic human resource management by positioning automatic patch work behavior as a new and meaningful entity and impacting that automatic patch work behavior allows for linking work behavior to organizational agility in an era of environmental uncertainty. Practical implications were identified through the ability of automatic patch work behavior directly or through the mediation of employees' dynamic capabilities and employee agility to encourage increased organizational agility. The locus of this research was conducted in government agencies, but this research model can also be replicated in business companies, so that employee characteristics (including automatic patch work behavior) in various workplaces in their contribution to organizational sustainability (including organizational agility) can be confirmed more comprehensively and represented, and equipped with ideas and research models that are always updated.